Growth and Yield Response of Maize (Zea mays L.) on Acid Soil to Different Rates of Humic Acid and NPK Fertilizer - Putri Wulandari; Endang Sulistyaningsih; Suci Handayani; Benito Heru Purwanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The main constraint in the extensification of maize on the dry land of acid soil is the low availability of P in soil. This study aimed to determine the effect and the optimal dose of humic acid on the growth and yield of maize on acid soil. This research was conducted from February to May 2017 at Tri Dharma Field Laboratory, Faculty of Agriculture, Gadjah Mada University. Acid soil with low P availability used was from sub-district Cigudeg and Jasinga, West Java. The research was arranged in Randomized Complete Block Design (RCBD) with 2 factors. The first factor was maize cultivar, namely Bisi 2 and Pioneer 35. The second factor was the rate of humic acid and NPK fertilizer, consisting of 0 kg.ha-1 (without) NPK and 0% (without) humic acid, NPK + 0% (without) humic acid, NPK + 5% humic acid, NPK + 10% humic acid, and NPK + 15% humic acid. NPK fertilizer applied was NPK 16:16:16 at a dose of 350 kg.ha-1. The results showed that humic acid application on acid soil increased C-humic content in the soil, soil P availability, total dry weight of the plant, and kernel dry weight at harvest (15 weeks after planting). The increase in soil P availability did not improve the plant growth but increased the accumulation of plant biomass. The application of humic acid at 15% (52.5 kg.ha-1) combined with NPK fertilizer on acid soil significantly increased total dry weight of plant and kernel dry weight up to 13.14% and 21.81%, respectively, thus, it is recommended for maize cultivation on acid soil.